MODEL PEMBELAJARAN STAD (STUDENT TEAM ACHIEVEMENT DIVISION) TERHADAP KEMAMPUAN MENYIMPULKAN ISI TEKS PERSUASIF - Lastri Sintauli Siahaan; Frinawaty Lestarina Barus (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to determine the Effect of the STAD (Student Team Achievement Division) Learning Model on the Ability to Summarize the Contents of Persuasive Texts of Class VIII Students of SMP N 4 Medan in the 2024/2025 Academic Year. The population in this study were all class VIII students totaling 332 people. The sample consisted of 60 people divided into two classes, namely the control class of 30 people and the experimental class of 30 people. This study used a two group post-test design experimental method using a quantitative approach. The instrument used in this study was an essay test. The results of the study showed 1) The ability to conclude the contents of persuasive texts of class VIII students of SMP N 4 Medan in the 2024/2025 Academic Year using conventional learning models still did not meet the KKM determined by the school, the results obtained by students with the conventional model, namely an average of 66, were classified as sufficient. 2) The ability to conclude the contents of persuasive texts of class VIII students of SMP N 4 Medan in the 2024/2025 Academic Year using the STAD learning model got improved results with an average of 84 classified as very good. Thus, it can be said that the value of the experimental class is higher than the value of the control class. Based on the t-test, the significance level value of α = 0.05 and n = 30 was obtained, ttable = 2.045. Thus, it can be concluded that tcount> ttable, namely, 7.70> 2.045, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant influence of the use of the STAD learning model on the ability to conclude the contents of persuasive texts of class VIII students of SMP N 4 Medan in the 2024/2025 Academic Year.